"It belongs to the world." Oil, conservation and futures in the making in Lofoten, Norway. (December 2019) - Karlsson, Marianne; Dale, Brigt
This article analyzes how debates on the potential exploration of petroleum, a World Heritage Application and the establishment of a national park in Lofoten, Northern Norway, have interacted between 2008 and 2017. By using an ontological security perspective on anticipation, we identify and analyze how local responses to petroleum and conservation processes diverge and connect over a cross-cutting set of concerns about the future. Through qualitative interviews and media analyses of local newspapers, we identify four themes of concerns over which the processes interact: the environment, jobs and demographic development, decision-making processes and livelihoods and identities. Our findings show that when played out in the same time period and geographic setting, the seemingly different development proposals of petroleum and conservation have become entangled and embedded in a broader discussion about what constitutes Lofoten today and how the region can be secured in the future. As such, the processes have mirrored each other's style of anticipation, demonstrated by that petroleum debates span the viability and identity of coastal communities and identities, and by that conservation initiatives focus on economic generation and job creation. We argue that anticipatory practices in Lofoten are funded upon the specific human–nature relationships that characterize the region, emerging through cross-cutting concerns related to the viability of fisheries, the existence of coastal communities and the possibility of self-determination. We approach these concerns as local manifestations of sources of ontological security that influence how any future in the making are imagined, supported and resisted in the region. The article adds new perspectives to current debates on how future development directions are envisioned and enacted locally by underlining the interrelationship between the search for ontological security and anticipatory practices.